The unfortunate miss: a saddle pulmonary embolism - Li, William; Gruca, Marek; Madhira, Bhaskara (International Journal of Medicine, 2017)
Pulmonary embolism is a potentially life-threatening condition that requires prompt diagnosis and efficient management such as in the form of thrombolysis or surgical thrombectomy. Saddle pulmonary emboli occurring at the bifurcation of the pulmonary artery are especially dangerous as they put afflicted individuals at risk for sudden hemodynamic collapse. While CT Angiography at present is the current imaging modality of choice, times exist when they are contraindicated and V/Q scintigraphy is used as the choice alternative. We present a rare catastrophic case of a saddle pulmonary embolism in an individual with a low-probabilityinterpretation on V/Q scintigraphy despite a clear depiction of the thrombus on echocardiography.